Effect of intervention time on quality and fatigue in paired CPR: a study with lifeguard - Brais Ruibal-Lista (2025)
Objective: This study compared two switch strategies during a 16-minute simulated CPR: every 2 minutes (as per ERC guidelines) versus self-paced switching based on perceived fatigue. Methods: Eighteen lifeguards completed three tests: a 2-minute individual CPR test and two 16-minute partner-based simulations, one with 2-minute changes and the other with self-selected changes. CPR quality (QCPR, QCC, QVR), heart rate (HR), and perceived exertion (RPE) were assessed. Results: Global CPR quality was significantly higher in the 2-minute switch protocol compared to the self-paced strategy. Fatigue markers (HR and RPE) were also lower with the standard approach. However, participants with better performance in the individual test were able to sustain longer interventions under the self-paced condition. Conclusion: Switching every 2 minutes results in better CPR quality and reduced fatigue. However, individual ability predicts performance in self-paced scenarios, supporting the potential of personalized protocols and training in lifeguard CPR interventions